INCREASING INNOVATIVE ACTIVITY IN TEACHERS IN THE PROCESS OF PROFESSIONAL DEVELOPMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article emphasizes that improving the innovative competencies of natural science teachers in the advanced training system is an important factor today. The role and importance of innovative competences of teachers is also emphasized, as well as their effective use in the formation of independent thinking.